An extensive investigation into the prevalence and the genetic and serological diversity of toxigenic Vibrio parahaemolyticus in Italian marine coastal waters. (14th August 2012) - Ottaviani, D.; Leoni, F.; Rocchegiani, E.; Mioni, R.; Costa, A.; Virgilio, S.; Serracca, L.; Bove, D.; Canonico, C.; Di Cesare, A.; Masini, L.; Potenziani, S.; et al.
Summary The relationship between Vibrio parahaemolyticus strains isolated from the aquatic environment and those isolated from cases of infection in humans is poorly understood due to the low prevalence of tdh‐ and/or trh‐positive strains in the environment. To address this concern, it would be useful to analyse the genetic relationships among environmental and food strains and with reference to clinical isolates, also applying molecular typing methods. The aim of this study was to evaluate the prevalence of toxigenic V. parahaemolyticus in Italian coastal waters and seafood, to examine intra‐species variability and to identify, using serotyping and pulsed‐field gel electrophoresis (PFGE), relationships among strains from different sources, geographical origin and period of isolation. Of the 192 V. parahaemolyticus strains isolated in different Italian areas and examined in this study, 25 (13.0%) proved to carry the trh gene while none of the strains proved positive to the search by PCR for tdh and Group‐Specific‐toxRS genes. The prevalence of toxigenic strains in the Tyrrhenian Sea was significantly lower than that calculated for the Ligurian coasts. Regarding the sources of isolation, the higher prevalence of trh‐positive V. parahaemolyticus was revealed in fish, followed by clams, plankton, oysters, mussels and lastly seawater. Within the toxigenic strains, 16 serotypes and 20 distinct PFGE patterns were identified. Two clusters, which included a total of 8 V. parahaemolyticus strains, were specifically associated with the North Adriatic Sea area and were stable over time. Our results demonstrate that trh‐positive V. parahaemolyticus strains circulated in Italy in the period 2002–2009 with a prevalence higher than that reported from other European and extra‐European countries, confirming that toxigenic V. parahaemolyticus is an emerging public health concern in Italy, regardless of its pandemic potential.